A Multiregional Impact Assessment Model for disaster analysis. Issue 4 (1st October 2016) - Koks, Elco E.; Thissen, Mark
ABSTRACT: This paper presents a recursive dynamic multiregional supply-use model, combining linear programming and input–output (I–O) modeling to assess the economy-wide consequences of a natural disaster on a pan-European scale. It is a supply-use model which considers production technologies and allows for supply side constraints. The model has been illustrated for three floods in Rotterdam, The Netherlands. Results show that most of the neighboring regions gain from the flood due to increased demand for reconstruction and production capacity constraints in the affected region. Regions located further away or neighboring regions without a direct export link to the affected region mostly suffered small losses. These losses are due to the costs of increased inefficiencies in the production process that have to be paid for by all (indirectly) consuming regions. In the end, the floods cause regionally differentiated welfare effects.